Piscivorous ichthyocomplex of the Velykoburluts’ke reservoir as a factor affecting the survivability of fish seeds of Chinese carps - I. Buzevych (Ribogospodarsʹka Nauka Ukraïni, 2020)
Purpose. To determine and analyze structural and quantitative parameters of piscivorous fishes of the Velykoburluts’ke reservoir with the assessment of trophic load on multiple-age juveniles of the silver and bighead carps and their hybrids.